Євген Маланюк і Дарія Віконська. Мистецька трансформація історії княжого роду Федоровичів у поемі "Побачення" - Набитович, І.Й. (Слово і Час, 2019)
Історія мистецьких контактів Євгена Маланюка та Дарії Віконської – фрагментарна й маловідома. У статті розглянуто поему “Побачення” Маланюка, у якій подана мистецька трансформація історії княжого роду Федоровичів. Князівський український рід Федоровичів розсіявся по Европі, творячи її історію, культуру, економічний розвиток. Лінія, яка закінчувалася Кароліною-Іванною Федорович-Малицькою, залишилася українською. Інші розчинилися в інших національних культурах (найчастіше польській). Karolina Ivanna Fedorovych-Malytska (1893–1945) came into Ukrainian writing and culture as Dariia Vikonska, the author of short prose, literary studies, critical reviews and art studies. She was close to the circle of ʻvisnykivtsiʼ (the ʻVisnyk-poetsʼ). The history of literary contacts between Yevhen Malaniuk and Dariia Vikonska remains fragmentary and little known. The paper focuses on the poem “Pobachennia” (“Meeting”) by Malaniuk that transforms the history of Fedorovyches family in an artistic way. Ukrainian princely family of Fedorovyches spread all over the Europe creating its history, culture and contributing to its economic development. The line in which Karolina Ivanna Fedorovych-Malytska was the last representative remained Ukrainian. Other lines dissolved in other national cultures (often Polish). Yevhen Malaniuk left a brief memoir about Dariia Vikonska within an episode of his visit to the estate of Malytskyis in Podillia region. Some fragments of conversations and reminiscences in the first part of the poem “Meeting” supplement the description of this visit. The poem was written in 1939–1941 and consists of three parts although its structure is somewhat obscure. The first part of the poem artistically describes the fate of the Ukrainian princely family of Fedorovyches in historiosophical perspective. This family is rooted in the history of the Grand Duchy of Lithuania and the Polish–Lithuanian Commonwealth. The second and third parts of the poem are oneiric visions of the lyrical character. The poet tells about the meeting with the general Vasyl Tiutiunnyk, the deceased chief of the Armed Forces Headquarters of the Ukrainian People’s Republic, and premonition of a mysterious meeting with already deceased parents and grandparents that should happen after the death of the character. The mystical third part of the poem describes the transition of the human soul to eternity in a lyrical literary way.